Modular Synthesis of Monomers for On-Surface Polymerization to Graphene Architectures - Gille, Marie; Viertel, Andreas; Weidner, Steffen; Hecht, Stefan (Synlett, 2013)
We developed a modular synthesis of halogenated polycyclic aromatic monomers for on-surface polymerization to generate graphene wires, ribbons, and networks.
Keywords: graphene monomers; graphene nanoribbons; functionalized graphene nanoribbons; graphene wires; hexabenzocoronene; on-surface polymerization